Safeguarding adults : a workbook for social care workers - Collins, Suzan (Knowledge and skills for social care workers series., 2009)
Working in residential or domiciliary settings involves a responsibility to safeguard adults from harm and abuse. This workbook will provide staff and relatives with the ability to make sensible choices concerning prevention and protection, as well as responding to and reporting concerns. Safeguarding Adults examines the different forms of abuse, where abuse can take place and how and where to report the suspected abuse. The workbook meets the requirements of care standards and promotes best practice by enabling staff to feel confident contributing to keeping the people they support safe from harm and abuse.